Effect of a non-peptide angiotensin receptor antagonist on water intake caused by centrally administered carbachol in the rat - Reis, L. C. [UNESP]; Saad, W. A. [UNESP]; Camargo, L. A.A. [UNESP]; Renzi, A. [UNESP]; Menani, J. V. [UNESP] (My University, 1996)
Angiotensin II (ANG II) administered centrally produces drinking by acting on subtype 1 ANG II (AT1) receptors. Carbachol, a cholinergic receptor agonist, also induces drinking behavior by a central action. In the present study we determined whether the response to carbachol also involves AT1 receptors. Male Holtzman rats (250-300 g) with stainless steel cannula implanted into the lateral ventricle (LV) were used. Water intake after injection of 0.15 M NaCl (1.0 μl) into the LV was 0.2 ± 0.01 ml/h (N = 8). The AT1 receptor antagonist DUP-753 (50 nmol/μl) injected into the LV reduced water intake induced by ANG II (10 nmol/μl) from 9.2 ± 1.4 to 0.4 ± 0.1 ml/h (N = 8), and water intake induced by carbachol (2 nmol/μl) from 9.8 ± 1.4 ml/h to 3.7 ± 0.8 ml/h (N = 8). These results suggest that AT1 receptors play a role in the drinking behavior observed after central cholinergic stimulation in rats.
Keywords: angiotensin II; angiotensin receptor antagonist; AT1 receptor; carbachol; DUP-753; water intake